Analisis Mikrobiologi Forensik Total Mikroba Sosis Sapi yang Bercampur Lemak Babi dalam Rangka Kehalalan Produk - Mariany Razali; Revi Trisna Siregar; Nurmala Sari; Maya Handayani Sinaga (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
Halalness of a food product is an important factor as a consideration in consuming it. Raw materials and additives used will affect the halality of the product. The food that we called to be halal if it does not contain pork including lard. This study was applied of the forensic microbiological analysis in assessing the total microbes contained in sausages containing lard. The aim of the study was to analyze the total microbes in beef sausages mixed with lard. In this total microbial analysis, a factorial Completely Randomized Design (RAL) method was used. Factor I is Solvent Concentration (K) which consists of four levels (K1 = 20%, K2 = 30%, K3 = 40%, K4 = 50%) and Factor II is Maseration Time (W) which consists of four levels (W1 = 6 Hours, W2 = 12 Hours, W3 = 18 Hours, W4 = 24 Hours). The results showed that the n-hexane concentration in beef sausage samples : lard (1: 1) gave a very significant effect (P> 0.01). The highest number of microbes was found in K1 (9487,500) and the lowest was in K4 (3887,500). The maceration time had a different effect that was not significant (P <0.05). The highest number of microbes is found at W4 (8475,000) and the lowest at W1 (5387,500). Treatment interactions had no significant effect (P <0.05).